Work ability in nursing: relationship with psychological demands and control over the work - Andrea Prochnow; Tânia Solange Bosi de Souza Magnago; Janete de Souza Urbanetto; Carmem Lúcia Colomé Beck; Suzinara Beatriz Soares de Lima; Patrícia Bitencourt Toscani Greco (Universidade de São Paulo, 2013)
OBJECTIVE: to evaluate the association between psychological demands, control over the work and the reduction of work ability of nursing professionals. METHOD: this cross-sectional study involved 498 nursing professionals of a university hospital in the State of Rio Grande do Sul, Brazil. Data collection was carried out in 2009 using the Brazilian versions of the Work Ability Index and Job Stress Scale, with logistic regression models used for the data analysis. RESULTS: the prevalence of 43.3% for reduced work ability and 29.7% for high-strain in the job (high psychological demand and low control) were observed. The chances for professionals presenting reduced work ability under high-strain were higher and significant when compared to those classified as being under low-strain, even after adjusting for potential confounders, except for age and gender. CONCLUSION: a high prevalence of reduced work ability was observed. This evidence indicates the need for investigation and detailed analysis of the psychosocial aspects of the professionals with regard to the health/disease process of nursing professionals.